2021
DOI: 10.3390/w13121670
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Model and Optimization of the Diclofenac Degradation Kinetic for Ozonation Processes Intensification

Abstract: This work focused on estimating the rate constants for three ozone-based processes applied in the degradation of diclofenac. The ozonation (Oz) and its intensification with catalysis (COz) and photocatalysis (PCOz) were studied. Three mathematical models were evaluated with a genetic algorithm (GA) to find the optimal values for the kinetics constants. The Theil inequality coefficient (TIC) worked as a criterion to assess the models’ deviation. The diclofenac consumption followed a slow kinetic regime accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…According to Table 3, most of the research was focused on the study of kinetic parameters from photocatalytic and electrochemical oxidation processes; meanwhile, no investigation related to the UV/H 2 O 2 kinetics was found. At the same time, there were not independent studies on the reaction kinetics of pure ozonation and Fenton processes, instead, these were intensified with photocatalysis [87] and electrochemical processes, [180] respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Table 3, most of the research was focused on the study of kinetic parameters from photocatalytic and electrochemical oxidation processes; meanwhile, no investigation related to the UV/H 2 O 2 kinetics was found. At the same time, there were not independent studies on the reaction kinetics of pure ozonation and Fenton processes, instead, these were intensified with photocatalysis [87] and electrochemical processes, [180] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[84][85][86] In addition, if a solid catalyst is included, adsorption phenomena should be considered. [87][88][89] Furthermore, the kinetic of the gas-liquid interactions is highly dependent on the target pollutants and their concentration, thus, the kinetic regime of the ozone consumption should be characterized in terms of the Hatta number (Ha) to accurately model the ozone transport from the gas to the liquid phase. [90] Ultraviolet/Hydrogen Peroxide Processes It has been observed that the presence of UV in combination to hydrogen peroxide can promote the generation of HO * radicals by means of the Haber-Weiss mechanism.…”
Section: Ozonationmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers demonstrated that the metal doped nanostructures and nano-compounds are increased and improved their catalytic activity and ability for adsorption of toxic gas molecules [23]. The metal doped on surfaces of nanostructures are catalytic positions and possible sites for adsorption of toxic gas molecules [24,25].…”
Section: Introductionmentioning
confidence: 99%